Protective role of Cocos nucifera L. water on BPA-mediated oxidative stress and reproductive damage in male rats. - Shafie, Nur Farah Shafinaz; Nurul Bashar, Nurul Kabir; Abd Aziz, Nor Azlina; Dasiman, Razif; Hashim, Noor Hashida (International Journal of Environmental Health Research, 2025)
Bisphenol A (BPA) may impair male fertility by inducing oxidative stress in the testis, though its effects on spermatogenesis and sperm quality remain unclear. Conversely, Cocos nucifera L. (coconut) water, rich in antioxidants, effectively inhibits oxidative stress. The aim of the study is to evaluate the protective effect of Cocos nucifera L. water against BPA-mediated oxidative stress in male rats. Thirty Sprague-Dawley rats were divided into control (C) received distilled water (0.5 mL/day), vehicle (V) received corn oil (0.5 mL/day), Bisphenol A (B) (50 mg/kg/day), Cocos nucifera L. water (CW) (10 mL/kg/day) and Cocos nucifera L. water plus bisphenol A (CW+B) groups. The testes and epididymis were harvested on day 31 for oxidative stress analysis, histological examination, immunofluorescence assay, and sperm motility. BPA administration reduced glutathione levels, increased malondialdehyde levels, and caused histopathological changes in the testis. Additionally, the grayscale intensity of actin and tubulin immunofluorescence, along with sperm motility, significantly decreased in the B group (p < 0.001). However, these parameters were notably improved by the administration of coconut water in CW+B group (p < 0.001). Conclusively, this study suggests that coconut water enhances antioxidant defences and supports male reproductive health in rats, potentially preventing BPA-induced reproductive damage.